2017
DOI: 10.1186/s12882-017-0630-6
|View full text |Cite
|
Sign up to set email alerts
|

The attenuation of renal fibrosis by histone deacetylase inhibitors is associated with the plasticity of FOXP3+IL-17+ T cells

Abstract: BackgroundThe histone deacetylase (HDAC) inhibitor, which has potential effects on epigenetic modifications, had been reported to attenuate renal fibrosis. CD4+ forkhead box P3 (FOXP3)+ T regulatory (Treg) cells may be converted to inflammation-associated T helper 17 cells (Th17) with tissue fibrosis properties. The association between FOXP3+IL-17+ T cells and the attenuation of renal fibrosis by the HDAC inhibitor is not clear.MethodsThis study evaluated the roles of the HDAC inhibitor, Treg cells and their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…But Tamassia noted that the human neutrophils are unable to express and produce IL-17A, IL-17B, or IL-17F in vitro ( 61 ). Our data show that IL-17A was mainly produced by CD4 + Tcell, rather than F4/80 + macrophages in UUO mice, which was consistent with previous reports ( 55 , 62 ).…”
Section: Discussionsupporting
confidence: 94%
“…But Tamassia noted that the human neutrophils are unable to express and produce IL-17A, IL-17B, or IL-17F in vitro ( 61 ). Our data show that IL-17A was mainly produced by CD4 + Tcell, rather than F4/80 + macrophages in UUO mice, which was consistent with previous reports ( 55 , 62 ).…”
Section: Discussionsupporting
confidence: 94%
“…From a mechanistic point of view, increasing evidence has suggested that HDAC3-deficient macrophages upon LPS stimulation could not activate almost half of the inflammatory gene expression 62 . For instance, it was reported that HDAC inhibition by TSA treatment and vorinostat impedes the conversion of regulatory T cells (Tregs) into IL-17 + Tregs 12,63 . This led us to hypothesize the effect of PPL on modulating HDAC expression.…”
Section: Discussionmentioning
confidence: 99%
“…An important epigenetic phenomenon in macrophages is the transient inflammatory stimulus-mediated changes that include histone deacetylase (HDAC) activation, which increases the production of pro-inflammatory cytokines in wide disease models, including septic shock, acute respiratory distress syndrome, renal fibrosis, and rheumatoid arthritis, where abrogation of HDAC activity reduced inflammatory cytokines [10][11][12] . Moreover, HDAC inhibition was found to suppress the polarization of T helper type 17 (Th17) cells and STAT3 inhibition 13 , while HDAC3 inhibition reduced TNF-α, with a concomitant increase in the acetylation of p65, which has been suggested to play a key role in attenuating IκΒαmediated NF-κΒ transcriptional activity [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…This may be a consequence of the fact that most rodent models of diabetes do not develop late-stage fibrotic changes that are typically associated with GFR decline [ 94 ]. That being said, broad-spectrum, class-specific or isoform-specific HDAC inhibitors have been reported to have anti-fibrotic effects in non-diabetic rodent models of renal fibrosis, including the unilateral ureteral obstruction model [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ] and the rat remnant kidney model [ 88 ]. Given that common pathogenetic mechanisms are often shared during the development of renal fibrosis, regardless of the etiology, it could be postulated that HDAC inhibition may confer similar benefits on later stage renal decline.…”
Section: Future Directionsmentioning
confidence: 99%